Beyond Trisambodo Scandal: How Taxpayers’ Perception And Knowledge Influence Their Compliance - Cendekiawan, Muslim; Suci, Saraswati Nirmala; Qadri, Resi Ariyasa (Educoretax, 2024)
This study is aimed to predict and explain the impact of taxpayers' perceptions of the Directorate General of Taxes and tax knowledge, moderated by taxpayer income level, on tax compliance, particularly in the aftermath of the Rafael Alun Trisambodo scandal. A distinctive feature of this study is the employment of perceptions of the Directorate General of Taxes as an independent variable, which is innovatively derived from text mining Twitter data, alongside the application of ordinal data for the taxpayer income variable. Employing a survey methodology, this research engaged with a diverse cohort of 133 taxpayer respondents. The analytical framework adopted herein is the structural equation modeling analysis, which facilitates a comprehensive examination of the relationships between the specified variables. The findings reveal a significant causality between taxpayers' tax knowledge and their compliance behavior, positing that an enhanced understanding of tax-related matters invariably leads to greater adherence to tax obligations. This outcome underscores the imperative for the Directorate General of Taxes to intensify efforts in the realm of taxpayer socialization and education, aiming to augment levels of tax compliance. The insights gleaned from this study are anticipated to serve as valuable inputs for the Directorate General of Taxes in formulating strategies to bolster tax compliance among the populace.